A - Atemweg: Übersicht, Indikation und Hilfsmitte - Küßner, Tobias; Popp, Erik (Notfall & Rettungsmedizin, 2017)
Under the special circumstances of emergency medicine, airway management is risky and fraught with complications. Despite being rarely necessary, securing the airway by endotracheal intubation or supraglottic airway devices is usually life-saving in these cases. The basis for this review is the algorithm for prehospital airway management. Some of the typical devices for safeguarding the respiratory tract are described and evaluated with regard to the current state-of-the-art, as found in the current literature. Simple measures such as the jaw thrust maneuver or inserting an Guedel or Wendl airway are often the first basic actions. Endotracheal intubation (ETI) remains the gold standard of airway management; nevertheless, it requires a high degree of expertise and is especially complex under the adverse conditions of emergency medicine. Supraglottic airway devices (SGA) are an effective alternative. In emergency medicine only laryngeal tubes or masks of the second generation should be used and cuff pressure should be controlled as early as possible. To facilitate ETI, the McCoy laryngoscope blade or video laryngoscopy can be used. Concerning the latter, the use of blades that alternatively allow direct laryngoscopy are recommended. Referring to cricothyrotomy, surgical techniques seem to have a slight advantage of being faster. Every operator should be familiar with the equipment that is locally available. For monitoring the position and effectiveness, capnography and oximetry must be used whenever ventilating a patient.
Gesehen am 26.11.2018